Claustral afferents of superior parietal areas PEc and PE in the macaque. Issue 6 (16th June 2016) - Gamberini, Michela; Passarelli, Lauretta; Bakola, Sophia; Impieri, Daniele; Fattori, Patrizia; Rosa, Marcello G. P.; Galletti, Claudio
ABSTRACT: The exposed surface of the primate superior parietal cortex includes two cytoarchitectonically defined areas, the PEc and PE. In the present study we describe the distribution of neurons projecting from the claustrum to these areas. Retrograde neuronal tracers were injected by direct visualization of regions of interest, and the location of injection sites was reconstructed relative to cytoarchitectural borders. For comparison, the patterns of claustral label that resulted from injections involving neighboring cytoarchitectonic areas were analyzed. We found that the claustral territories sending projections to areas PE and PEc partially overlapped zones previously shown to form projections to the posterior parietal, somatosensory, visual, and motor cortex. The projection zones to the PE and PEc overlapped extensively, and consisted of multiple patches separated by label‐free zones. Most of the labeled neurons were located in the posterior–ventral part of the claustrum. Area PE received additional inputs from a posterior–dorsal part of the claustrum, which has been previously reported to project to the somatosensory cortex, while the PEc receives additional input from an anterior–ventral region of the claustrum, which has been reported to project to the visual association cortex. These observations reflect the known functional properties of the PE and PEc, with the former containing neurons that are predominantly involved in somatosensory processing, and the latter including both somatosensory and visual neurons. The present results suggest that the claustrum projections may help coordinate the activity of an extensive neural circuit involved in sensory and motor processing for movement execution. J. Comp. Neurol. 525:1475–1488, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Superior parietal areas PE and PEc of the macaque brain receive afferents from the claustrum, an enigmatic subcortical structure. The claustral territories overlapped extensively and most of the labeled neurons were located in the posteroventral part of the claustrum. This claustral region is known to be involved in neural circuits for sensory and motor processing.